Islamic Value-Based Integration of the National Curriculum: A Model for Enhancing Science Learning in Islamic Boarding Schools - Een Junaenah; St. Wardah Hanafie Das; Rayamangsi; Abdul Halik; Muhammad Sain (Postgraduate, University of Mataram, 2026)
This study analyzes and formulates a model for integrating the Islamic values-based pesantren curriculum with the national curriculum at DDI Al-Munawwaroh Merauke. Many Islamic boarding schools struggle to balance religious education with national academic standards, resulting in curriculum overlap and excessive student learning burden. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and documentation with key informants including school leadership, teachers, and students. Data analysis followed the Miles, Huberman, and Saldana interactive model, with validity verified through source and method triangulation. Findings indicate that curriculum integration is implemented systematically through structural and functional approaches encompassing planning, organizing, implementing, and evaluating learning. Integration is realized through schedule synchronization, cross-curricular teacher collaboration, integrated teaching materials, and internalization of Islamic values across all subjects and activities. Unlike institutions that run religious and general curricula in parallel, the proposed model offers a structured, contextual strategy aligned with Merauke’s socio-cultural conditions. This produces a holistic, adaptive educational system meeting national standards while addressing local challenges. The study provides practical implications for Islamic boarding schools in developing effective curriculum integration strategies, confirming that planned and contextual integration successfully balances academic achievement with Islamic character formation.